2019
DOI: 10.1016/j.na.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Well-posedness results for a class of semi-linear super-diffusive equations

Abstract: In this paper we investigate the following fractional order in time Cauchy problemThe fractional in time derivative is taken in the classical Caputo sense. In the scientific literature such equations are sometimes dubbed as fractional-in time wave equations or super-diffusive equations. We obtain results on existence and regularity of local and global weak solutions assuming that A is a nonnegative self-adjoint operator with compact resolvent in a Hilbert space and with a nonlinearity f ∈ C 1 (R) that satisfie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…where A is a differential operator which generates a strongly continuous semigroup on L 2 ðXÞ. Detailed results can be found in [1,3,8,12]. Let 1 p\1 and q 1 ; q 2 2 ½1; 1 be given constants.…”
Section: Moreover X¼mentioning
confidence: 99%
“…where A is a differential operator which generates a strongly continuous semigroup on L 2 ðXÞ. Detailed results can be found in [1,3,8,12]. Let 1 p\1 and q 1 ; q 2 2 ½1; 1 be given constants.…”
Section: Moreover X¼mentioning
confidence: 99%
“…For more explicit relation between H s () and H s (), one can consult Alvarez et al, 24 where it has been established that…”
Section: Preliminarymentioning
confidence: 99%
“…For more explicit relation between Hsfalse(scriptBfalse) and sfalse(scriptBfalse), one can consult Alvarez et al, 24 where it has been established that s(B)=Hsfalse(scriptBfalse)=H0sfalse(scriptBfalse)if0.3em0<s<12H0012false(scriptBfalse)if0.3ems=12H0sfalse(scriptBfalse)if0.3em12<s<1 with H0s(B):=D(B)true‾Hs(B). Here, scriptDfalse(scriptBfalse) denotes the space of infinitely differentiable functions with compact support in scriptB. The space H0012false(scriptBfalse) is concerned with the particular case s = 1/2.…”
Section: Mathematical Aspectsmentioning
confidence: 99%
“…In [30], Metzler-Klafter showed that non-Markovian diffusion processes with a memory can be modeled by a time fractional diffusion equation. These time fractional equations have become a primary component in the fields of partial differential equations and has attracted much attention; see for example [27,18,3,13,21,15,19,30].…”
mentioning
confidence: 99%